Maternal Delta Hemoglobin between the First and Third Trimesters as a Risk Factor for Low Birth Weight: A Cohort Study - Silva-Rengifo, Christian (2021)
Objetive: The present study focused on determining if the hemoglobin difference of the third and first trimester of gestation greater than - 1 (decreased hemoglobin delta) is a risk factor for low birth weight in term newborns at Hospital Belen from Trujillo. Material and Methods: We performed a retrospective cohort study in which 218 newborns were included according to the selection criteria. The patients were divided into two group of patients with decreased and non-decreased maternal hemoglobin delta: applying the relative risk and the statistical chi test-square. Results: The frequency of low birth weight in pregnant women with decreased hemoglobin delta was 32/109 = 29%; the frequency of low birth weight in pregnant women with undiminished delta hemoglobin was 18/109 = 17%. Declined maternal hemoglobin delta is a risk factor for low birth weight with a relative risk of 1.78 [CI: 95% (1.45 - 3.56) p <0.05]. Conclusions: The decreased maternal hemoglobin delta is a risk factor for low birth weight in newborns at Hospital Belen de Trujillo.